Design of data-injection adversarial attacks against spatial field detectors - R. López-Valcarce; Daniel Romero (IEEE Workshop on Statistical Signal Processing (SSP), 2016)
Data-injection attacks on spatial field detection corrupt a subset of measurements to cause erroneous decisions. We consider a centralized decision scheme exploiting spatial field smoothness to overcome lack of knowledge on system parameters such as noise variance. We obtain closed-form expressions for system performance and investigate strategies for an intruder injecting false data in a fraction of the sensors in order to reduce the probability of detection. The problem of determining the most vulnerable subset of sensors is also analyzed.
Keywords: adversarial signal processing; compass; wsn